Performance Trends of Hotels and Casino Hotels Through the Recession: An ARIMA With Intervention Analysis of Stock Indices. Issue 1 (2nd January 2016) - Zheng, Tianshu; Farrish, John; Kitterlin, Miranda
Abstract : This study used Autoregressive Integrated Moving Average with Intervention analysis technique to examine weekly stock indices of the hotel segment and the casino hotel segment in comparison with the S&P 500 index. The results indicate that casino hotel firms were affected at the beginning of the recession and hotel firms and S&P 500 firms were not affected until nine months later. In addition, this study performed multiple t-tests to compare the average financial ratios between the two hotel segments to reveal changes in financial structures through the recession. The findings of this study may help industry practitioners and investors cope with future economic downturns and fill a gap in the existing literature by demonstrating the process of identifying lag time of an impact using ARIMA with Intervention Analysis technique.